Aconselhamento pastoral em meio a crises de doença e morte - Schulz, Carmita (2009)
In this work we present a study of Practical Theology s discipline, with the analysis of the pastoral counseling ahead of crises caused by illness that leads to the death. The first part treats the death, as the last stage of the life, searching to understand the cases of grave diseases; the death; the behavior of the human being together with its familiar ones; its attitudes; thoughts; the silence and the hope. And the human being s behavior during a grave illness until the death. The second part relates to the crisis generated by the terminal illness; the definition and the types of crises; how to deal with the crises. We speak, also, on the survival of the families after losses, especially, being a crisis that culminated in death, using it as growth factor. We analyze the pastoral relation, its objectives and methods of support in case of crises by the terminal illness. The third and last part brings a small record of the history of the pastoral counseling; some historical contributions; as counseling became and as it arrived until us. Some forms of boarding with dying and its families, and how this can be used with diseased in the threshold of the death. We verify that in almost all the situations with sick terminals and death, the human being needs some counseling.